2015
DOI: 10.1371/journal.pone.0122397
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Shugan Jianpi Zhixie Therapy for Diarrhea-Predominant Irritable Bowel Syndrome: A Meta-Analysis of Randomized, Double-Blind, Placebo-Controlled Trials

Abstract: BackgroundShugan Jianpi Zhixie therapy (SJZT) has been widely used to treat diarrhea-predominant irritable bowel syndrome (IBS-D), but the results are still controversial. A meta-analysis of randomized, double-blind, placebo-controlled trials was performed to assess the efficacy and tolerability of SJZT for IBS-D.MethodsThe MEDLINE, EMBASE, Cochrane Library, the China National Knowledge Infrastructure database, the Chinese Biomedical Literature database and the Wanfang database were searched up to June 2014 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…215 One formulation known as Shugan Jianpi Zhixie had 7 trials of 954 IBS-D patients. 216 Another formulation known as Tongxie Yaofang had 23 publications involving 1972 IBS-D patients. 217 A very recently published RCT had 1044 patients with Rome III criteria IBS randomized to 3 treatments for 4 weeks, and found that Tongxie Yaofang was significantly better than placebo for improving abdominal pain and stool parameters, but not better than pinaverium for abdominal pain.…”
Section: Grade Of Evidence: Highmentioning
confidence: 99%
“…215 One formulation known as Shugan Jianpi Zhixie had 7 trials of 954 IBS-D patients. 216 Another formulation known as Tongxie Yaofang had 23 publications involving 1972 IBS-D patients. 217 A very recently published RCT had 1044 patients with Rome III criteria IBS randomized to 3 treatments for 4 weeks, and found that Tongxie Yaofang was significantly better than placebo for improving abdominal pain and stool parameters, but not better than pinaverium for abdominal pain.…”
Section: Grade Of Evidence: Highmentioning
confidence: 99%
“…Moreover, sub-classification of IBS was also left out of consideration. The other study was a meta-analysis of Shugan Jianpi Zhixie therapy for IBS-D [ 9 ]. Although this sub-classification was taken into consideration, placebos were adopted in control groups.…”
Section: Introductionmentioning
confidence: 99%
“…Shugan-Jianpi, a traditional Chinese medicine (TCM) terminology, which means the method of soothing the liver (Shugan) and invigorating the spleen (Jianpi), is widely used in treating liver and gastrointestinal diseases [ 11 , 12 ]. Chaihu–Shugan–San (CSS), the representative of Shugan (soothing liver) recipes, can treat gastrointestinal diseases and depression-related diseases [ 13 , 14 ], while Shenling–Baizhu–San (SLBZS), the representative of Jianpi (invigorating spleen) recipes, can regulate intestinal flora and treat gastrointestinal related diseases [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%